2015
DOI: 10.21002/jepi.v16i1.457
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Jaminan terhadap Peluang Memperoleh Kredit bagi UMKM di Sumatera Barat

Abstract: Collateral Effect to Bank Loan Probability for Microenterprises in West SumateraThis paper reveals that West Sumatera banking sector are more likely using the availability of collateral for the credit to micro, small and medium enterprises (MSME). Using 384 sample size from MSME in West Sumatera, if a MSME have enough collateral, the probability of their credit application to be rejected by banks will fall from 59.9% to 11.7% comparing to they don’t have enough collateral. This finding proved a credit guarante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
1
6
0
1
Order By: Relevance
“…Some previous research has found that collaterals are becoming a major consideration for banks to accept or refuse credit requests (Jaswadi et al, 2015). Collaterals were the main reason for rejecting and accepting credit requests for micro small medium enterprises in West Sumatera (Marta & Satria, 2015). Non-availability of collaterals was the main reason for them not to borrow from banks (Badan Pusat Statistik Provinsi Sumatera Barat, 2019).…”
Section: Validity and Reliability Testsmentioning
confidence: 99%
“…Some previous research has found that collaterals are becoming a major consideration for banks to accept or refuse credit requests (Jaswadi et al, 2015). Collaterals were the main reason for rejecting and accepting credit requests for micro small medium enterprises in West Sumatera (Marta & Satria, 2015). Non-availability of collaterals was the main reason for them not to borrow from banks (Badan Pusat Statistik Provinsi Sumatera Barat, 2019).…”
Section: Validity and Reliability Testsmentioning
confidence: 99%
“…Hal ini sejalan dengan penelitian yang dilakukan terhadap 384 UMK di Sumatera Barat. Hasil penelitian ini menyatakan bahwa peluang sebuah aplikasi kredit yang diajukan UMK ditolak akan berkurang dari 59,9% menjadi 11,7% jika UMK tersebut memiliki jaminan yang cukup (Marta & Satria, 2016).…”
Section: Gambar 4 Persentase Industri Pengolahan DI Kabupaten Kebumen...unclassified
“…Collateral is an asset used as security for a loan. Collateral is critical for entrepreneurs to access external financing because it provides security for the lender and reduces their risk [19], [29]. However, many entrepreneurs in Indonesia may not have sufficient collateral to secure loans, especially for large loans.…”
Section: Collateralmentioning
confidence: 99%
“…Credit guarantees refer to assets that can be pledged to obtain loans. In Indonesia, the availability of credit guarantees is a major barrier in accessing external loans for entrepreneurs, as many entrepreneurs do not have enough assets to use as collateral [19]- [21].…”
Section: Introductionmentioning
confidence: 99%